Safety of High-Dose Intravenous Daptomycin Treatment: Three-Year Cumulative Experience in a Clinical Program - Figueroa, D. A.; Mangini, E.; Amodio-Groton, M.; Vardianos, B.; Melchert, A.; Fana, C.; Wehbeh, W.; Urban, C. M.; Segal-Maurer, S. (Clinical infectious diseases, 2009)
Background.There are limited safety data for high-dose and long-term daptomycin treatment (>6mg/kg administered for ⩾14 days). We present our experience in 61 patients. Methods.We performed a retrospective chart review for all patients treated with daptomycin at New York Hospital Queens (Flushing) from 1 January 2004 through 30 April 2007; patients were identified through a computerized hospital pharmacy database. Results.Sixty-one patients (29 male and 32 female patients; mean age, 66.6 years) received a mean dose of 8 mg/kg of daptomycin for a median of 25 days (range, 14-82 days). Twelve patients (with bone and skin and soft-tissue infections) did not have an identified microbiologic isolate. Gram-positive infections included bloodstream infection with or without infective endocarditis (n=32), skin and soft-tissue infection (n=14), bone and joint infection (n=9), and intra-abdominal infection (n=5), and unidentified infection (n=1). Prosthetic devices were removed from 11 of 20 patients. Grade 1 adverse events occurred in 22 patients and did not lead to daptomycin discontinuation. Fifty-eight patients underwent creatine phosphokinase (CPK) analysis (34 patients had paired CPK analyses at the beginning of and during therapy, and 13 patients had random CPK analysis performed during treatment). Three patients had constitutional and/or musculoskeletal symptoms accompanying CPK levels >10 times upper limit of normal (grade 3). All occurred after 24 days of treatment and improved after daptomycin treatment was discontinued. Two of 3 patients were morbidly obese (body mass index grade III). Conclusions.Daptomycin treatment was well tolerated at a mean dose of 8 mg/kg for a median duration of 25 days. The incidence of symptomatic CPK level elevation was within the range reported with lower doses of daptomycin and/or for shorter treatment durations.